Identification Of Landslide-Prone Areas In Citeureup Sub-District, Bogor Regency, West Java, Indonesia - Hizkia Tuejeh; Muzani; Ilham Badaruddin Mataburu; Lyzia Nabilla (Jurnal Geografi, Edukasi dan Lingkungan (JGEL), 2023)
There were 21 landslides in Citeureup Subdistrict in 2017-2021 which caused several houses to be slightly damaged to severely damaged, and road and bridge infrastructure was cut off. This study aims to identify landslide-prone areas in Citeureup Sub-District. The method used was descriptive method with a spatial approach. Data was processed using GIS 10.8 software with the analytical technique used was a spatial analysis by overlaying five parameters of landslide susceptibility. After that, field validation was carried out. The subjects in this study were 12 selected land units. The results showed that areas that are included in the category of low landslide prone are Citeureup, Leuwinutug, Puspanegara, Puspasari, Sanja, and West Karangasem and East Karangasem Villages. The distribution of areas in the landslide-prone category is in a small part of Hambalang Village, Sanja, East Karangasem Village, and Leuwinutug Village. The distribution of areas in the high landslide-prone category is in most of Hambalang, Tajur, and Tangkil Villages. The distribution of areas in the landslide-prone category is very high in most of Hambalang, Tangkil, Sukahati, and a small part of it in East Karangasem Village. The distribution of landslide-prone areas is dominated by areas in the high landslide-prone category. Meanwhile, the distribution of landslide-prone areas is at least found in the medium landslide-prone category area.